(untitled) (The Pretoria Student Law Review, 2021)
This research will thus consider whether or not section 22 of CPA is inconsistent with the spirit, purport and object of the Constitution. To provide a brief overview of this paper; the introduction will illuminate the aim of the research followed by an examination of what constitutes ‘search’ and ‘seizure’ in terms of CPA. The paper will thereafter consider the existing jurisprudence on search and seizure operations and elucidate the manner in which search and seizure operations affect certain rights in the Bill of Rights. An examination of search and seizure operations under Canadian law will be conducted with the paper culminating in a conclusion containing recommendations regarding the enforcement of search and seizure operations.